The behavior of arsenic trioxide in non-ferrous extractive metallurgical processing. Issue 2 (3rd June 2014) - Sadegh Safarzadeh, M.; Miller, J.D.; Huang, H.H.
Abstract : Study of the acid bake-leach process has shown potential advantages for the treatment of enargite (Cu3 AsS4 ) concentrates. Among the most important advantages of the process is the transformation of enargite to water-soluble copper sulfate and highly soluble arsenic trioxide (arsenolite). Because arsenic is retained in the condensed phase during the baking, the vapor pressure of arsenic trioxide should be estimated at typical baking temperatures (e.g. 473 K). To that end, the vapor pressure of As4 O6 (g) was estimated under the baking conditions based on published thermodynamic values. The vapor pressure of arsenolite at 473 K was found to be approximately 9.03 × 10 -4 atm. Based on the linear regression analysis of the published vapor pressure values for arsenolite in the temperature range 366−579 K, the equation for the best fit line was found to be as follows, with a correlation coefficient of 0.9973: log P Arsenolite (atm) = (-5780.7)/( T (K))+9.16. Available information on arsenic trioxide does not allow a definite conclusion regarding the arsenolite/claudetite transformation temperature and their exact melting points. However, the transition temperature has been reported to be in the wide range of 240−506 K in different references. Furthermore, the thermodynamic information concerning arsenolite/claudetite is sparse and at times not consistent. An effort has been made in this paper to compile the most reliable thermodynamic information for arsenic trioxide (arsenolite and claudetite).